FROM SUBSTANCE USE TO ALGORITHMIC CONTROL: NEW PARADIGMS IN THE PSYCHOLOGY OF ADDICTION - Mo‘minxo‘jayeva Zuhra Alimjon qizi (American Journals Publishing, 2025)
This article analyzes the stages in the development of the psychology of addiction and elucidates the intrinsic interconnections among chemical, behavioral, and digital–algorithmic forms of addiction. The study examines the neurobiological and biopsychosocial foundations of addiction, with particular attention to the dopaminergic reward system and the impact of contemporary digital technologies and artificial intelligence on human behavior. Addiction to artificial intelligence is interpreted as a new and complex phenomenon within modern psychology.
Keywords: Addictive behavior; chemical addiction; behavioral addiction; digital addiction; addiction to artificial intelligence; dopaminergic reward system; biopsychosocial model; algorithmic control.